ESTIMATES OF SOLUTIONS OF THE ONE CLASS OF OPERATOR EQUATIONS - Копач, Михайло Іванович; Обшта, Анатолій Феліксович; Шувар, Богдан Антонович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In this paper it is proved some theorem on existence of solution in a class of differential equation x = Fx in semi-ordered Banach space E and given some estimations for the solutions.